2019
DOI: 10.3390/nano9091247
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Few-Layer MoS2 in the Pores of Mesoporous Carbon Hollow Spheres for Lithium-Sulfur Batteries

Abstract: Integrating a highly conductive carbon host and polar inorganic compounds has been widely reported to improve the electrochemical performances for promising low-cost lithium sulfur batteries. Herein, a MoS2/mesoporous carbon hollow sphere (MoS2/MCHS) structure has been proposed as an efficient sulfur cathode via a simple wet impregnation method and gas phase vulcanization method. Multi-fold structural merits have been demonstrated for the MoS2/MCHS structures. On one hand, the mesoporous carbon hollow sphere (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Zhao et al de-signedM oS 2 /MCHS as the sulfur cathode, which has an excellent entrapment capability and high conductivity. [56] It is also found that the integration of heteroatom-doped carbon can furtheri mprove the performance of MoS 2 for LiÀS batteries. According to DFT calculations and the results of diffusion experiments,P araknowitsch and Thomas revealed that the chemical interactions between Li 2 S x and carbon materials could be enhanced by heteroatom doping, such as N, S, and B.…”
Section: Mos 2 /Carbon3ds Tructural Cathodesmentioning
confidence: 96%
See 1 more Smart Citation
“…Zhao et al de-signedM oS 2 /MCHS as the sulfur cathode, which has an excellent entrapment capability and high conductivity. [56] It is also found that the integration of heteroatom-doped carbon can furtheri mprove the performance of MoS 2 for LiÀS batteries. According to DFT calculations and the results of diffusion experiments,P araknowitsch and Thomas revealed that the chemical interactions between Li 2 S x and carbon materials could be enhanced by heteroatom doping, such as N, S, and B.…”
Section: Mos 2 /Carbon3ds Tructural Cathodesmentioning
confidence: 96%
“…Zhao et al. designed MoS 2 /MCHS as the sulfur cathode, which has an excellent entrapment capability and high conductivity …”
Section: Structural Designmentioning
confidence: 99%
“…8 Proposed adsorption mechanism of polysulfides for the (a) MCHS/S and (b) MoS 2 /MCHS/S electrodes. 35 Other researchers have also [49][50][51][52][53] devoted their attention to the application of core-shell structured MoS 2 nanocomposites. The double-layer core-shell structure has good prospects.…”
Section: Research Situation Of Mos 2 As a Cathode Materials Of Li-s Bamentioning
confidence: 99%
“…Although the effectiveness of the strategies, some amount of polysulfides still dissolved in the electrolyte and thus giving rise to the performance degradation. [27][28][29][30][31][32] This means that complete inhibition of the shuttle effect remains a big challenge for LiÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Through strong chemical interactions between the polar moieties and polysulfides, the shuttle effect was significantly suppressed and the resulting sulfur cathodes realized a long cycling life. Although the effectiveness of the strategies, some amount of polysulfides still dissolved in the electrolyte and thus giving rise to the performance degradation . This means that complete inhibition of the shuttle effect remains a big challenge for Li−S batteries.…”
Section: Introductionmentioning
confidence: 99%